The dismissal of public-school educators on the grounds of sexual abuse of children : an appraisal of section 188a of the Labour Relations Act 66 of 1995 - Van Eck, B.P.S. (University of Pretoria, 2025)
Thesis (LLD (Mercantile Law))--University of Pretoria, 2025.